Representasi Identitas Budaya Madura dalam Lagu Karya R. Amiruddin Tjitraprawira Kajian Semiotika (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to uncover semiotic meanings and representations of cultural identity in traditional Madurese songs composed by R. Amiruddin Tjitraprawira, using Ferdinand de Saussure’s semiotic approach. The research focuses on two songs, “Tanduk Majeng” and “Asta Aermata,” selected for their rich portrayal of cultural, historical, and religious values of the Madurese community. A descriptive qualitative method was employed, using the Miles and Huberman model of data analysis, including data reduction, data display, and conclusion drawing. The findings reveal that the signifiers and signifieds in the lyrics represent key aspects of Madurese cultural identity, such as the work ethic of seafarers, reverence for ancestors, religious values, and communal solidarity. Additionally, local symbols like the sea, sailboats, and royal tomb complexes serve as strong representations of the community’s collective meaning-making. The study implies that traditional songs function not only as entertainment but also as a medium for preserving cultural values and ethnic identity. This research is expected to contribute to the development of semiotic studies on regional music and support the preservation of Madurese cultural heritage through linguistic and cultural approaches.